Competition between a transmembrane helix on Scap and a membrane cholesterol regulates Scap–Insig interaction and SREBP activation - Blake C. Williams; Daniel L. Kober; Xiao-chen Bai; Daniel M. Rosenbaum; Arun Radhakrishnan (Proceedings of the National Academy of Sciences, 2026)
Cholesterol homeostasis in mammalian cells relies on the interaction between two endoplasmic reticulum (ER) sterol-sensing membrane proteins, Scap and Insig. Their interaction regulates activation of transcription factors called sterol regulatory element–binding proteins (SREBPs) that control genes for cholesterol biosynthesis and uptake. Previous studies suggested a model where cholesterol sensing by Scap involves communication across the ER membrane between two functional domains, a cholesterol-binding domain on the luminal side and a COPII-binding domain on the cytosolic side. When ER cholesterol is low, Scap binds COPII adapter proteins to facilitate ER-to-Golgi transport and proteolytic activation of SREBPs. When ER cholesterol is above a threshold concentration, this transport is blocked, a process that requires Insigs. However, the precise molecular mechanisms by which cholesterol and Insigs control the conformations of Scap remain unknown. Here, we elucidate the 3.2 Å cryo-EM structure of a Scap/Insig complex in the presence of saturating amounts of cholesterol. Structure-guided mutagenesis of the Scap/Insig interface indicates that Scap’s transmembrane helix 7 (TM7) plays a critical role in transducing conformational changes between the luminal and cytosolic sides of the ER membrane to control Scap/SREBP transport from ER to Golgi. An intramembrane cholesterol bound at the Scap/Insig interface competes with the intramolecular interaction of Scap’s TM7 at this interface to modulate cholesterol sensing. These results further advance our understanding of how Scap senses cholesterol and provides additional targets for controlling cholesterol and lipid synthesis in the context of metabolic diseases and even some cancers.